In vivo monitoring of carbonic anhydrase expression during the growth of larval zebrafish: a new environment-sensitive fluorophore for responsive turn-on fluorescence. Issue 76 (25th August 2020) - Chou, Chih-Hung; Wu, Chang-Yi; Chen, Chun-Lin; Zhou, Jun-Qing; Kao, Yu-Chen; Chen, Hsing-Yin; Lin, Po-Chiao
Abstract : A customized DQI fluorophore promises in vivo monitoring of carbonic anhydrase expression during the growth of larval zebrafish by responsive fluorescence enrichment. Abstract : This study monitors the dynamic progress of a newly developed background-free, target responsive strategy; 2, 3-dihydroquinolin-4-imine (DQI) that can instantly respond to environmental changes with fluorescence enhancement, revealing a comprehensive platform for in vivo fluorescence bioimaging of mebrane-bound carbonic anhydrase II in HeLa cells and its expression during the growth of larval zebrafish.